Vulnerable Decision Points for Disproportionate Office Discipline Referrals: Comparisons of Discipline for African American and White Elementary School Students. (August 2016) - Smolkowski, Keith; Girvan, Erik J.; Mcintosh, Kent; Nese, Rhonda N. T.; Horner, Robert H.
Racial disparities in rates of exclusionary school discipline are well documented and seemingly intractable. However, emerging theories on implicit bias show promise in identifying effective interventions. In this study, we used school discipline data from 1, 666 elementary schools and 483, 686 office discipline referrals to identify specific situations in which disproportionality was more likely. Results were largely consistent with our theoretical model, indicating increased racial and gender disproportionality for subjectively defined behaviors, in classrooms, and for incidents classified as more severe. The time of day also substantially affected disproportionality. These findings can be used to pinpoint specific student-teacher interactions for intervention.